Science and technology for integrated rural development : proceedings of the COSTED seminar, Madras, India, March 7-8, 1977 - Radhakrishna, S. (International Council of Scientific Unions, COSTED (Committee on Science and Technology in Developing Countries), 1977)
Comprises papers relating to South and Southeast Asian Region.